Research Progress on Phytochemicals from Mulberry with Neuroprotective Effects: A Review - Junwei Chen; Zhonglang Gou; Yufei Huang; Qianhui Yu; An Na Kim; Wenchao Shi; You Zhou (Pharmaceuticals)
With the intensification of the population aging worldwide, neurological disorders (NDs) are seriously threatening human society. Mulberry, a traditional economic crop, is a significant medicinal plant. Increasing evidence suggests that phytochemicals from mulberry play critical roles in the prevention and treatment of NDs. This paper reviews the recently reported phytochemicals from mulberry with neuroprotective effects and systematically summarizes neuroprotective mechanisms and their classifications. Based on their origins from different parts of mulberry, the extracts with neuroprotective effects are classified into mulberry fruit extract and mulberry leaf extract. According to the compound structures, the compounds are divided into flavonoids, Diels–Alder-type adducts (DAAs), benzofurans, quinones, stilbenes, and alkaloids. This aims to provide a future reference for their pharmaceutical development and utilization.